Determinants of job dissatisfactions and turnover intention among employees in Malaysian private institution / Nur Shafini Mohd Said ... [et al.] - Mohd Said, Nur Shafini; Wahab, Muhamad Syaiful Hakimie; Omar Ali, Siti Rapidah; Mat, Khalid Amin (2018)
Nowadays, turnover is one of big problems occurred in any organizations and it is shared in every type and size of organization at every organizational level. Staff turnover becomes a serious issue especially in the arena of human resources supervision. The study examined the relationship between three elements of staff' job dissatisfactions towards employees' turnover intention. For this study, the researchers have selected the staff of Malaysian Private Institution as the population being studied which involved 113 respondents. For the purpose of data collection, the questionnaire was used as the main instrument. The questionnaire comprises of 3 segments which includes section A: demographic background, section B: determinants of job satisfactions and section C: staff job satisfaction. All the items needed in the questionnaire were developed concurring to the research questions and research objectives. For this study, the simple random sampling was selected among the staff. This is because of the method was the most efficient for the probability sampling design. Other than that, the method is easily understood and the results are being projected to the whole population. After several times of follow-ups, total numbers of 113 questionnaires were received out of a total number of 150 questionnaires. The SPSS was applied for the analysis of data statistically. The Correlation Analysis and multiple regressions were utilized to identify the relationship among job dissatisfactions towards staff turnover intention. Based on the findings, the hypotheses were accepted. Thus, the findings confirmed that all hypotheses have positive relationships between independent variables toward staff turnover intention. Finally, the researchers hope that the findings can give benefits to the organization as well.